OC-044 Mucosa-Associated E.coli Isolates from Inflammatory Bowel Disease and Colorectal Cancer Patients Activate Wnt/Beta-Catenin Signalling in vitro and in vivo. (17th August 2016) - Meehan, B; Campbell, BJ; Rhodes, JM
Abstract : Introduction: Increased numbers of adherent, invasive E.coli (AIEC) have been reported within intestinal epithelium of patients with Crohn's disease (CD) and colorectal cancer (CRC). 1 Genotoxicity and angiogenic activity of AIEC have been described by our group and others. 2–4 We hypothesised that a key contribution of cancer-promoting activity of AIEC may also be through their ability to activate Wnt/b-catenin signalling, and reported that Wnt target-genes were up-regulated in colonocytes at mRNA and protein level, including cyclooxygenase-2 (COX-2). 5 Here, we further investigated the ability of AIEC to activate Wnt transcription and nuclear translocation of b-catenin. We sought also to confirm our findings in vivo using an AIEC mono-association mouse model. Methods: Activation of Wnt transcription activity in response to E.coli isolates 1 (MOI: 10; for 4 h) was assessed using a TCF/LEF HeLa cell luciferase reporter assay. Infected cells were also pre-treated with and without COX inhibitors. Nuclear translocation of b-catenin was assessed by immunofluorescence in CRC cell-lines SW480 and DLD1. Following 6 week mono-association of Il10 -/- 129 SvEv mice with CRC AIEC isolate HM44, intestinal tissue was fixed, Cox-2 and β-catenin expression assessed by immunohistochemistry and compared to germ-free controls. Results: Mucosa-associated E.coli isolated from CRC (HM44, HM358, HM545), Crohn's disease (HM95, HM605), and ulcerative colitis (HM250, HM374) patients significantly increased Wnt TCF/LEF signalling in HeLa cells, ranging from 1.56±0.11 to 2.60±0.06 fold above uninfected controls (1.0±0.03); all p < 0.001, Kruskal-Wallis. Infection of SW480 and DLD1 showed significant increases in b -catenin nuclear translocation as per prostaglandin E2 treatment (1–10 μM). These responses were blocked using COX inhibitors (diclofenac>indomethecin>aspirin; 1–100 μM). Increased intestinal Cox-2 expression and Wnt signalling was observed in vivo in Il10 -/- mice infected with E. coli HM44 (n = 15) compared to germ-free mice (n = 5), with Cox-2 elevated 2.04±0.10 fold, and nuclear localisation of β-catenin elevated 1.98±0.13 fold; both p < 0.001; Mann-Whitney U. Conclusion: IBD and CRC mucosa-associated E.coli activate intestinal Wnt-signalling in vitro and in vivo. The specific bacterial factors triggering early cancer-promoting signals such as elevated COX-2 and Wnt pathway activation are currently being investigated using a validated CRC E.coli fosmid-library screening approach, 3 with 12 confirmed positive clones currently undergoing sequence analysis. References: 1 Martin HM, et al . Gastroenterology 2004;127 :80–93 2 Arthur JC, et al . Science 2012;338 :120–23 3 Prorok-Hamon M, et al . Gut 2014;63 :761–70 4 Buc E, et al . PLoS One 2013;8 (2):e56964 5 Meehan B, et al . Gut 2015;64 (Supp 1):A362–A363 (abstract) Disclosure of Interest: B. Meehan: None Declared, B. Campbell Conflict with: Has received honoraria from Amgen, Falk and Enterome, J. Rhodes Conflict with: Is/has been a member of advisory boards for Atlantic, Procter & Gamble and Falk, has received honoraria from Abbott, Falk, Ferring, Glaxo Smith Kline, Procter & Gamble and Schering Plough.